2022
DOI: 10.1177/02537176221140557
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Quality of Life in Patients Treated with Single Infusion Tocilizumab for COVID-19: A Follow-up, Controlled Study

Abstract: Background: The inflammatory state that characterizes COVID-19 may contribute to depression, anxiety, other morbidities, and mortality. Interleukin-6 blocker tocilizumab has been used as a treatment modality in COVID-19 as an anti-inflammatory agent. Tocilizumab has also been studied for its potential use in preventing depression in other patient groups, with mixed results. This study was designed to study subsequent depression, anxiety, and quality of life (QOL) in patients treated with tocilizumab plus stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These observations should again raise attention concerning the appropriateness of using IL-6 receptor inhibitors in patients with COVID-19, given that these agents would raise the serum level of IL-6, which can predispose to the development of long COVID [ 5 ]. Our hypothesis is supported by a recent study [ 6 ] investigating the subsequent development of depression and anxiety, and quality of life in patients with moderate to severe COVID-19 treated with tocilizumab versus no tocilizumab. It was observed that patients in the tocilizumab group had significantly more depressive and anxiety symptoms, and a worse quality of life than the controls at a 3-month follow-up.…”
supporting
confidence: 79%
“…These observations should again raise attention concerning the appropriateness of using IL-6 receptor inhibitors in patients with COVID-19, given that these agents would raise the serum level of IL-6, which can predispose to the development of long COVID [ 5 ]. Our hypothesis is supported by a recent study [ 6 ] investigating the subsequent development of depression and anxiety, and quality of life in patients with moderate to severe COVID-19 treated with tocilizumab versus no tocilizumab. It was observed that patients in the tocilizumab group had significantly more depressive and anxiety symptoms, and a worse quality of life than the controls at a 3-month follow-up.…”
supporting
confidence: 79%
“…Another study was carried out in patients with moderate to severe COVID-19-related pneumonia after their discharge. Subjects receiving tocilizumab in adjunct to the standard treatment showed marginally worse levels of depression than those undergoing the standard treatment only at the 3-month follow-up, whereas an absence of depression was observed at the 6-month follow-up [47]. Sarilumab has not been assessed for its effects on depression, but one study on subjects with rheumatoid arthritis showed more effectiveness on depression as compared to adalimumab [48].…”
Section: Introductionmentioning
confidence: 99%